If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 4n + -6(4m + -4n) = 0 3m + 4n + (4m * -6 + -4n * -6) = 0 3m + 4n + (-24m + 24n) = 0 Reorder the terms: 3m + -24m + 4n + 24n = 0 Combine like terms: 3m + -24m = -21m -21m + 4n + 24n = 0 Combine like terms: 4n + 24n = 28n -21m + 28n = 0 Solving -21m + 28n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-28n' to each side of the equation. -21m + 28n + -28n = 0 + -28n Combine like terms: 28n + -28n = 0 -21m + 0 = 0 + -28n -21m = 0 + -28n Remove the zero: -21m = -28n Divide each side by '-21'. m = 1.333333333n Simplifying m = 1.333333333n
| 3.5m-3.4-4.5m=9.5-1m-12.9 | | 3(3x+4)-2x-9=5 | | x^3-11x^2-4x+1=0 | | x=0.4(456-0.6(456-x)) | | 4x+29=6x+7 | | -8m^3+10m=0 | | 4(2x^2-3x+5)= | | 6-3x=-3x-6 | | 4(2m-2n)+3(7m+n)= | | 30+10x=6x+10 | | x=0.4(4.56-0.65(4.65-x)) | | .5(4r+2)=0 | | 2w^3+3w^2-10w-15= | | 5(x)=3x^2-3x | | 7=-4x+2 | | 4.6q-5.9-5.5q=-1.9q-2.4 | | 3x-2=-6 | | 12-3x=3(4-x) | | v=lah | | 3(x-4)-2x-8=5 | | 4x+5y=-32 | | 300=6b+240 | | r-.5(4r+2)=0 | | p+p+16+3p-24=872 | | 3n=17-n | | (3+v)(2v+7)=0 | | 12.50+4.50(x-3)=62.00 | | 3a+7=7 | | (3-x)(x+6)=0 | | 800-765= | | 10x-11=39 | | 4k^2+20k-2=0 |